MENGUJI DESAIN PEMASARAN TERHADAP KEPUTUSAN PEMBELIAN PROVIDER TELKOMSEL(STUDI EMPIRIS KONSUMEN DI KOTA SOLO) - Rifka Islamiati; Muhammad Jalari (Universitas Prof. Dr. Hazairin SH, 2021)
The aim of the researcher is to examine and find out some of the factors that are considered to have an effect on the purchasing decision of the telkomsel provider. Marketing design which includes variables of brand image, price, promotion has an effect onpurchasing decisions of Telkomsel providers. The method used is purposive sampling. This research population used unlimited population because it is not known exactly how many consumers. The sample was taken using the Roscoe formula with the number of respondents 40. The analysis technique was using multiple linear regression. With the results of the marketing design, brand image, price, and promotion variables simultaneously influence purchasing decision variables. Partially, there is a positive and significant influence on the brand image variable on purchasing decisions. There is a negative but significant effect on the price variable on purchasing decisions. There is a positive and significant influence on the promotion variable on purchasing decisions